2020
DOI: 10.3389/fpsyg.2020.553880
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-Being, Marital Satisfaction, and Parental Burnout in Iranian Parents: The Effect of Home Quarantine During COVID-19 Outbreaks

Abstract: Coronavirus disease 2019 (COVID-19), as an infectious disease, is now prevalent in many countries around the world, which has recently led many governments to home quarantine and impose penalties for violating quarantine. Concerns and stress caused by lockdown and social isolation led to personal and interactive reactions in some families, which are also culturally important to address. This study was administrated to study the psychological well-being and the effect of home quarantine on marital satisfaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 84 publications
(125 reference statements)
3
48
1
1
Order By: Relevance
“…Although men could objectively still do less than their female partners, they felt that the parental role was draining their emotional resources like never before. These findings may complement previous studies that have shown that fathers are more likely to experience burnout, even before the risks outweigh their resources, because they use up a lot of their resources in new situations [18,21,17].…”
Section: Family Burnout and Covid-19supporting
confidence: 86%
See 1 more Smart Citation
“…Although men could objectively still do less than their female partners, they felt that the parental role was draining their emotional resources like never before. These findings may complement previous studies that have shown that fathers are more likely to experience burnout, even before the risks outweigh their resources, because they use up a lot of their resources in new situations [18,21,17].…”
Section: Family Burnout and Covid-19supporting
confidence: 86%
“…A survey of families in the United States and the United Kingdom found that housework, childcare responsibilities, and the role of teaching children put a strain on parents, especially mothers. Such situations increase the risk of negative mood symptoms, depression, anxiety and stress in parents as well as symptoms of parental burnout [17].…”
Section: Family Burnout and Covid-19mentioning
confidence: 99%
“…The results of a study on Iranian parents reported, however, that home quarantine nearly one and a half months after the COVID-19 outbreak did not have a significant effect of parental burnout [32]. Taken together, these results suggest that the lockdown due to the COVID-19 outbreak seems to affect the mechanisms of parental stress and burden of parents differently.…”
Section: Fundingmentioning
confidence: 85%
“…A study that examined the impact of the COVID-19 pandemic in relation to parental stress among 183 parents in the western United States reported that parents experienced cumulative stressors due to the COVID-19 lockdown, including general stress and symptoms of depression and anxiety [ 4 ]. The results of a study on Iranian parents reported, however, that home quarantine nearly one and a half months after the COVID-19 outbreak did not have a significant effect of parental burnout [ 32 ]. Taken together, these results suggest that the lockdown due to the COVID-19 outbreak seems to affect the mechanisms of parental stress and burden of parents differently.…”
Section: Introductionmentioning
confidence: 99%
“…The parents' ability to perform both their professional and family roles during the COVID-19 crisis was challenged, new responsibilities being imposed on them by the new way of (tele-)working and their children's distance learning. This especially affected mothers, being the ones assuming these responsibilities (Mousavi, 2020 ). Mothers were at greater risk of suffering from parenting-related exhaustion in Italian culture, very similar to the Romanian one, both being of Latin origin, which still hold that women should be the primary caregiver to their children, while also managing their household and having some sort of career (Marchetti et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%